EFEKTIFITAS PENGEMBANGAN BAHAN AJAR ILMU PENDIDIKAN ISLAM BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW MELALUI KEGIATAN DESIMINASI PADA STAIS DDI MAROS - Bahraeni, Bahraeni (Universitas Islam Negeri Alauddin Makassar, 2017)
Abstract: This research is the result of research of development of teaching materials of Islamic education which is done through dissemination activity with problem How is the effectiveness level of the utilization of teaching materials of Islamic education in STAIS DDI Maros? The goal is to describe the level of effectiveness of the use of teaching materials of Islamic education that has been developed based on jigsaw type cooperative learning model. The effectiveness level of development of teaching materials of Islamic education based on jigsaw type cooperative learning model through the dissemination activity of normalized gain value equal to 0.77 high category. The response of lecturers to the modules and other learning tools obtained the average value of 3.80 categories is very good. Student response to the module and other learning tools obtained the average value of 3.71 categories is very good. The activity of lecturers to manage the learning obtained the average value of 3.90 categories is very good, and student activity obtained the average value of 1.68 with the category of very active students follow the learning process.